Probiotic adhesion to skin keratinocytes and underlying mechanisms - Lizardo, Mariana (2022)
The effects of probiotics on the skin are not yet well understood. Their topical application and benefits derived thereafter have recently been investigated. Improvements in different skin disorders such as atopic dermatitis, acne, eczema, and psoriasis after their use have, however, been reported. One of the mechanisms through which such benefits are documented is by inhibiting colonization by skin pathogens. Bacterial adhesion is the first step for colonization to occur; therefore, to avoid pathogenic colonization, inhibiting adhesion is crucial. In this study, invasion and adhesion studies have been carried out using keratinocytes. These showed that Escherichia coli is not able to invade skin keratinocytes, but adhered to them. Lacticaseibacillus rhamnosus and Propioniferax innocua decreased the viable counts of the three pathogens under study. L. rhamnosus significantly inhibited S. aureus adhesion. P. innocua did not inhibit pathogenic bacteria adhesion, but when added simultaneously with S. aureus (competition assay) a significant adhesion reduction (1.12 ± 0.14 log10CFU/mL) was observed. Probiotic bacteria seem to use carbohydrates to adhere to the keratinocytes, while S. aureus uses proteins. Lacticaseibacillus rhamnosus showed promising results in pathogen inhibition in both in vitro and ex vivo experiments and can potentially be used as a reinforcement of conventional therapies for skin dysbiosis. View Full-Text